2012
DOI: 10.1044/1092-4388(2012/11-0250)
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prelinguistic Phonological Categories

Abstract: Purpose The prelinguistic infant’s babbling repertoire of syllables—the phonological categories that form the basis for early word learning—is noticed by caregivers who interact with infants around them. Prior research on babbling has not explored the caregiver’s role in recognition of early vocal categories as foundations for word learning. In the present work, the authors begin to address this gap. Method The authors explored vocalizations produced by 8 infants at 3 ages (8, 10, and 12 months) in studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 62 publications
2
30
1
3
Order By: Relevance
“…The coders independently watched the videos, counting both syllables and canonical syllables in real time. This procedure is utilized regularly in the laboratories of the last author in accord with reasoning presented in recent papers, especially Ramsdell et al (2012). This naturalistic listening approach mimics how a mother would hear her child, listening to each utterance only once.…”
Section: Methodsmentioning
confidence: 99%
“…The coders independently watched the videos, counting both syllables and canonical syllables in real time. This procedure is utilized regularly in the laboratories of the last author in accord with reasoning presented in recent papers, especially Ramsdell et al (2012). This naturalistic listening approach mimics how a mother would hear her child, listening to each utterance only once.…”
Section: Methodsmentioning
confidence: 99%
“…The nonlinear measures revealed developmental trends: we observed a trend toward lower stability and less multiscale dependency in utterance timings. Together, these might index a growing capability on the part of SW to use vocalizations in communicative interaction with other individuals (Jaffe et al, 2001; Ramsdell et al, 2012). The decrease in %DET suggests a diversification of utterance timing patterns over time (Fusaroli and Tylén, under review), while the decrease observed in AF indicates a decline in endogenous vocalization-fluctuations over time toward a more locally determined pattern of vocalization timing (e.g., Kuznetsov and Wallot, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases the recordings were made during natural interactions of parents and sometimes experimenters with infants. The data selected here overlapped with but were not identical to the data used in any of several prior studies drawn from these archives (Buder, Chorna, Oller, & Robinson, 2008; Chen & Kent, 2009, 2010; Oller et al, 2013; Ramsdell, Oller, Buder, Ethington, & Chorna, 2012). …”
Section: Methodsmentioning
confidence: 99%